ChemInform Abstract: 2‐Vinyl Threoninol Derivatives via Acid‐Catalyzed Allylic Substitution of Bisimidates. Issue 43 (October 2015) - Kumar, Varun; Klimovica, Kristine; Rasina, Dace; Jirgensons, Aigars
Abstract Diastereoselective cyclization of 2‐butene‐1, 4‐diol bis(trichloroacetimidates) affords 4‐vinyloxazolines, which can be converted into threonine derivatives containing a quarternary carbon center.